Clinical Characteristics of Atrial Fibrillation in Saudi Women Cohort and Its Clinical Impact in a Tertiary University Hospital - Kamal W. AlGhalayini, (Journal of King Abdulaziz University: Medical Sciences, 2023)
A retrospective study was conducted to evaluate the characteristics of atrial fibrillation in a cohort of Saudi women, and its impact on morbidity. A complete medical history was obtained and all participants underwent a complete review of clinical data including electrocardiogram, echocardiogram, blood pressure measurement, and thyroid examination. The following laboratory examinations were performed: international normalized ratio; thyroid stimulating hormone; triiodothyronine; thyroxine; total cholesterol; triglyceride; low-density and high-density lipoprotein. A history of hospitalizations, stroke and in-hospital mortality were recorded. We recruited 84 women; the mean age was 61.8 years and the mean body mass index was 28.45 kg/m2. The mean hemoglobin level of the patients was 12.2 g/dL and the mean thyroid stimulating hormone level was 3.75 mIU/L. The target international normalized ratio was achieved in 58% of treated patients; 70% of the under target International Normalized Ration patients had been hospitalized more than once and 19% had suffered a stroke. Overall, international normalized ratio demonstrates gaps in the management of women with atrial fibrillation, and the negative impact on patient outcome, indicating the need to tailor treatment plans to the goals and requirements of these patients.